Análisis de indicadores de desarrollo de la educación ambiental en el cantón Machala provincia de El Oro - Arízaga Macas, Joselyn Anabel (My University, 2021)
Within the Development and Land Management Plan PDOT, in the Socio-Cultural component, there is the program to promote responsibility, social and environmental awareness, specifically in the environmental education project file, the same as when carrying out an in-house visit. situ to the Municipality of the Canton Machala, I was able to show the lack of management in the Department of Environmental Education and Animal Welfare, since the project has not been carried out, but only guided by the ordinance "Binational student contest of stories and Coastal ”, for this reason, since there are no indicators in the project, I will carry out my present study, which is based on the analysis of the development indicators of environmental education, through the recommended proposals of different executing entities, it should be emphasized that due to the non-existence of these indicators in the Canton, I propose an approach to a proposal of possible EA indicators, taking advantage of the Canton's environmental problems, to promote the development of values and new attitudes towards a sustainable environment among citizens. The main objective of this work is to analyze the development indicators of environmental education, through a comparative matrix, in order to promote sustainable development towards the environment among citizens. Likewise, I used a mixed research approach, that is, the qualitative method, the same one that helped me to compare the indicators from various bibliographic sources; and quantitative, since it allows us to evaluate the performance of the indicator processes.
Dentro del Plan de Desarrollo y Ordenamiento territorial PDOT, en el componente Socio-Cultural, se encuentra el programa para promover responsabilidad, conciencia social y ambiental, específicamente en la ficha de proyecto de educación ambiental, el mismo que al realizar una visita in situ al Municipio de el Cantón Machala, pude evidenciar la falta de gestión en el departamento de Educación Ambiental y Bienestar Animal, ya que no se ha realizado el proyecto, sino solo se guían de la ordenanza “Concurso binacional estudiantil de cuentos y leyendas de filo costero”, por tal motivo, al no existir los indicadores en el proyecto, realice mi presente estudio, el cual se basa en el análisis de los indicadores de desarrollo de educación ambiental, por medio de las propuestas recomendadas de diferentes entidades ejecutoras, cabe recalcar que debido a la inexistencia de estos indicadores en el Cantón, propongo un planteamiento de una propuesta de posibles indicadores de EA, acogiéndome a los problemas ambientales del Cantón, para promover en la ciudadanía el desarrollo de valores y nuevas actitudes hacia un medio ambiente sostenible. El principal objetivo del presente trabajo es Analizar los indicadores de desarrollo de educación ambiental, mediante una matriz comparativa, con el fin de promover en la ciudadanía el desarrollo sostenible hacia el medio ambiente. Así mismo, utilice un enfoque investigativo mixto, es decir el método cualitativo, el mismo que me ayudo a comparar los indicadores de varias fuentes bibliográficas; y cuantitativo, ya que nos permite evaluar el rendimiento de los procesos de los indicadores.
Keywords: INDICADOR; EDUCACION AMBIENTAL; PROBLEMA; MACHALA